Gender Role In Food Rights And Sovereignty In West Africa: A Rapid Review. - Addo, P.; Djekic-Ivankovic, M.; Abdu, A.; Boadi, P.; et al (African Scholarly Science Communication Trust, 2024)
Recognizing the critical role gender plays in food systems within West Africa, this review paper explores the contributions women make throughout the food value chain and the challenges they face in achieving food and nutrition security. A search across the databases; Hinari, Ovid MEDLINE, Scopus and Web of Science targeted peer-reviewed articles reporting on studies published between 2000 and 2023 in English or French and focused on women in West Africa. Data were extracted using a predefined form in Covidence and a narrative synthesis was used to summarize women’s roles and challenges within food systems. Thematic analysis of 69 peer reviewed articles out of a total of 9,789 screened revealed West African women as central figures in regional food systems. Beyond their well-documented roles in land preparation, planting, and harvesting, women actively engage in processing, distribution, marketing and household consumption of diverse food crops (fruits, vegetables, grains and tubers) across rural and urban agri-food systems. This multifaceted engagement extends far beyond production, demonstrably impacting key socio-economic and nutrition metrics including food security, food sovereignty, and sustainable livelihoods of countless communities across the region. Nonetheless, women are disproportionately affected by challenges such as unequal access to resources, limited decision-making power, and restrictive cultural norms and education. These factors hinder their participation in different activities within the food system. To address these gendered disparities and promote equitable food systems, targeted interventions are crucial. These interventions must prioritize education and training to equip women with knowledge, skills, and modern technology. Additionally, policy changes are necessary to promote equitable access to resources, financing and land ownership. Furthermore, dismantling discriminatory cultural norms and promoting gender equality are essential steps along with implementing infrastructure and technologies that address women's specific needs. By prioritizing women's empowerment through a combination of education, policy changes, technological upgrades, and collaborative efforts with stakeholders, West Africa can strive towards a more sustainable and equitable food system for all.
Research Article
Keywords: West Africa; Food Justice; Food Sovereignty; Gender Dynamics; West Africa; Food Systems